2011
DOI: 10.1007/s00394-011-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of JNK1, JNK2, and ligase Itch on reactive oxygen species formation and survival of prostate cancer cells treated with diallyl trisulfide

Abstract: These results suggest that JNK1-dependent increase in LIP is mediated by Itch ubiquitin ligase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The mechanism by which DATS causes ROS production has been investigated previously and involves elevation of labile iron pool due to ferritin degradation in an c-jun NH 2 -terminal kinase-dependent manner [3638]. A role for the adapter protein p66Shc in DATS-induced ROS production was also demonstrated recently [37].…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism by which DATS causes ROS production has been investigated previously and involves elevation of labile iron pool due to ferritin degradation in an c-jun NH 2 -terminal kinase-dependent manner [3638]. A role for the adapter protein p66Shc in DATS-induced ROS production was also demonstrated recently [37].…”
Section: Discussionmentioning
confidence: 98%
“…First of all, we observed that DATS-induced ferritin H degradation was significantly attenuated in PNT1a cells. In the case of ferritin L we did observe a small increase in the level of this protein in PNT1A cells, whereas as reported before, in PC-3 cells a significant decrease was observed (6). A downregulation of ferritin level by increased degradation or decreased biosynthesis of the protein leads to the elevation of labile iron pool (15).…”
Section: Discussionmentioning
confidence: 66%
“…We demonstrated that DATS treatment led to JNK-dependent phosphorylation and activation of p66Shc, and ligase Itch. The activation of this signaling pathway leads to ferritin degradation, an increase in LIP and iron-dependent ROS formation (6,7). Therefore one of the goals of this study was to evaluate if such signaling pathways would be activated in noncancerous prostate cell line after DATS treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DATS has been shown to induce cell cycle arrest by enhancing generation of reactive oxygen species (ROS) [ 33 , 34 , 43 , 45 , 47 ]. One pathway of ROS generation begins with degradation of the iron storage protein ferritin, which has been shown following DATS treatment, leading to an increase in labile iron pool (LIP) size [ 43 , 47 , 48 ]. Then, through the Fenton/Haber-Weiss reaction, free ferric iron reacts with superoxide and hydrogen peroxide to form hydroxyl radicals and hydroxide ions [ 34 , 49 ].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%